Upland rice varieties in Malaysia: Agronomic and soil physico-chemical characteristics - Musa, Mohamed Hanafi; Azemi, Hartinie; Juraimi, Abdul Shukor; Tengku Muda Mohamed, Mahmud (Universiti Putra Malaysia Press, 2009)
Rice production is a large industry and there are a lot of opportunities which can be obtained from it. Recently, the demand for specialty and high quality rice has increased remarkably, owing to the affluent and health conscious consumers in Malaysia. The research on upland rice has been neglected because of its low yield, though it has many good characteristics, including good fragrance and long grains. Furthermore, it has the advantage of being cultivated on dry land without accumulation of water. Therefore, a large track of idle lands in Malaysia can be developed for this purpose. This study involves a documentation of upland rice in natural conditions. Basic information on the varieties of upland rice which produce high grain yields and quality (fragrance, colour) was collected from selected locations in Peninsular Malaysia, Sabah, and Sarawak. For this purpose, both soil and plant materials (at harvest) were collected. The soil and plant materials were analysed for their macro- and micro-nutrient contents. Standard agronomic characteristics, during growing period and at harvesting time, were also measured. The data were analysed using the SAS statistical software and the mean values were then compared using the Duncan’s New Multiple Range Test (DMRT) at 0.05 level of significance. Seventeen upland rice fields were identified in several locations during the course of this survey. Thirty-five (35) varieties of upland rice seeds were successfully collected. In particular, upland rice and forest soil (as a control) were acidic, contain low nitrogen content and CEC value at 0 – 20 and at 20 – 40 cm depth. Higher Fe content was also observed, with a major limitation for the growth of upland rice. Ageh, Kendinga, and Strao varieties were selected for further evaluation on nutrient requirements using an idle land soil, owing to its growth cycle, productivity, and seed availability.